Media Intellectualism or Lived Catastrophe? Mediating and Suspending the A/political Act - Konior, Bogna M. (Identities: Journal for Politics, Gender and Culture, 2018)
Piotr Szczęsny set himself on fire in protest of the Polish government in October 2017. Charged with political orientation, his selfimmolation posed a challenge to the news media, forcing it deep into the gutter the suicide archive, where commentators debated appropriate aesthetics of protest in a country whose imagery imagery is predominately thanatic; in a nation-state that has been resurrected after its many occupations yet still remains within a sacrificial grave, with death as the cornerstone of community. In this article, I situate Szczęsny’s death within the nightmare-bound post-Soviet political scene through historically contextualizing the debate around his suicide, where the act itself was criticized on the basis of its inappropriate aesthetics of irrational selfharm. I argue that such binding of a/political catastrophe in a bundle of representations corresponds to what François Laruelle calls media intellectualism, a form of engaging suffering that relies on its mediation. Seeking an alternative discourse of engaging the a/political act, I look to Katerina Kolozova’s non-standard politics of pain and to Oxana Timofeeva’s work on “the catastrophe.” These positions, which I call stances of the unsubject, offer us different starting points for creating solidarity in spaces of void, pain and depression. For the unsubject, pain is the prerequisite for forming the political, albeit in a non-standard manner, where politics cannot oscillate around representations, ideologies or identities. Rather than mediate self immolation, I ask whether the way that we define “the political” could benefit from a subtraction of mediation, from a catastrophic thinking in parallel with the brutality of the real, rather than the repetition of (national) trauma. Author(s): Bogna M. Konior: Title (English): Media Intellectualism or Lived Catastrophe? Mediating and Suspending the A/political Act Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 166-185 Page Count: 20 Citation (English): Bogna M. Konior, “Media Intellectualism or Lived Catastrophe? Mediating and Suspending the A/political Act,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 166-185.